2007
DOI: 10.1002/dneu.20507
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase and calbindin delineate sex differences in the developing hypothalamus and preoptic area

Abstract: Throughout the hypothalamus there are several regions known to contain sex differences in specific cellular, neurochemical, or cell grouping characteristics. The current study examined the potential origin of sex differences in calbindin expression in the preoptic area and hypothalamus as related to sources of nitric oxide. Specific cell populations were defined by immunoreactive (ir) calbindin and neuronal nitric oxide synthase (nNOS) in the preoptic area/anterior hypothalamus (POA/AH), anteroventral perivent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 67 publications
9
80
0
Order By: Relevance
“…NO has been shown to regulate multiple physiological processes, particularly in mammals (6,12,15,18,22,31). These reports reflect that one of the important roles of NO in higher eukaryotes is the regulation of reproduction in males and females.…”
Section: Morphological Studiesmentioning
confidence: 87%
“…NO has been shown to regulate multiple physiological processes, particularly in mammals (6,12,15,18,22,31). These reports reflect that one of the important roles of NO in higher eukaryotes is the regulation of reproduction in males and females.…”
Section: Morphological Studiesmentioning
confidence: 87%
“…Since NO cannot be stored in synaptic vesicles, unlike other neurotransmitters, mechanisms that regulate its synthesis in time and space are crucial in determining its biological effect (Garthwaite, 2008). In the mouse (Clasadonte et al, 2008;present study), as in the rat (Grossman et al, 1994;Herbison et al, 1996), GnRH neurons are surrounded by NO-synthesizing neurons in the basal forebrain, one of the major sites of NOS expression in the CNS (Bredt et al, 1991;Yamada et al, 1996;Edelmann et al, 2007). The production of neuronal NO in the vicinity of GnRH neurons is tightly regulated by estrogens (d 'Anglemont de Tassigny et al, 2007a;Parkash et al, 2010) and has been shown to directly modulate GnRH neuronal activity (Clasadonte et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, these receptors can regulate gene expression, and many hormone-dependent sex differences in gene expression have been identified, including in the sex hormone receptors themselves and the enzyme aromatase that converts testosterone into 17b-oestradiol [10][11][12][13][14][15][16][17][18][36][37]40]. For example, we have used genetic strategies to visualize the expression pattern of aromatase in the brain and discovered that it is expressed in a few discrete areas, including the posterodorsal MeA (MeApd) and the posteromedial part of medial division of the BNST (BNSTmpm).…”
Section: (B) Sex Differences In Gene Expressionmentioning
confidence: 99%